Multifunctional Cellulose and Cellulose-Based (Nano) Composite Adsorbents - Shi, Ru-Jie; Wang, Tian; Lang, Jia-Qi; Zhou, Nong; Ma, Ming-Guo (Frontiers in Bioengineering and Biotechnology, 2022)
In the recent years, facing the improvement of the quality of environmental problem, the cellulose and cellulose-based (nano)composites received dramatically attention as adsorbents. In the review article, we first reported the recent advance on the adsorbents produced by modification and functionalized of cellulose. Furthermore, adsorbents produced by modification and functionalized of carboxymehyl cellulose are also covered. In addition, the cellulose-based (nano)composites as adsorbents are reviewed in detail. Finally, the future developments of cellulose and cellulose-based (nano)composites are put forward in environmental fields. In this review article, a critical comment is given based on our knowledge. It is believed that these biomass adsorbents will play more and more important roles in the applications of environmental fields.